(3eNJUQ LGeY GdCUhds - (3eLghds; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi ChOYJ gPG GdcJGH CMGOjK Yf QShd Gddg Udi Gddg Ydjg hSde hPdc eG EfJNHJg ef GdcJGH GdeSei LGeY GdCUhd ai CMGOjK GdQShd hgh jLeY GdcJH GdSJI s
(3BNQgG (B:s
(3J CfS bGd bGd QLd dQShd Gddg UdYe EYbdgG hCJhcd hCWdbgG hCJhcd abGd EYbdgG hJhcd CNQLg GdJQePi Je GdcJGH s
(3HBNQg hbajI HGSe GdSjO JGL GdOjf Ydi eOQSI CHj YeQ bOS Gddg SQIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3CUhd Gdabgs